2020
DOI: 10.4028/www.scientific.net/msf.990.127
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Activation Energy of Commercial Grade H<sub>2</sub>O<sub>2 </sub>from DSC for Using Evaluation Thermal Hazard

Abstract: Hydrogen peroxide is a strong oxidizing agent containing a peroxide functional group that easily decomposes. In this research, a commercial grade of 35 % w/w hydrogen peroxide was evaluated for thermal hazard and reactivity by differential scanning calorimetry (DSC). It was found that the calculated activation energy was 70.03 kJ/mol. The risk assessment of thermal hazard evaluated in terms of the adiabatic decomposition temperature rise at heating rate 2, 4 and 8 °C/min, were 236.5, 159.2 and 217.5 K, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For example, Wang Jianna [20] and others studied the thermal decomposition characteristics and thermal risk of methyl hydrazine sulfate by differential scanning calorimetry (DSC), calculated the kinetic characteristics of the decomposition process by Friedman method, and considered that the decomposition process followed the n-order kinetic model. Yabei Xu et al [21] studied the Autocatalytic Decomposition Characteristics and thermal decomposition of benzoyl peroxide by differential scanning calorimetry (DSC), and calculated the kinetic parameters of the decomposition process by Kissinger method; Suranee [22] et al Evaluated the thermal hazard and reactivity of hydrogen peroxide with a mass concentration of 35% by DSC. It is found that the calculated activation energy is 70.03 kJ/mol, and the adiabatic temperature rise at heating rates of 2,4,8℃/min is 236.5,159.2,217.5k.…”
mentioning
confidence: 99%
“…For example, Wang Jianna [20] and others studied the thermal decomposition characteristics and thermal risk of methyl hydrazine sulfate by differential scanning calorimetry (DSC), calculated the kinetic characteristics of the decomposition process by Friedman method, and considered that the decomposition process followed the n-order kinetic model. Yabei Xu et al [21] studied the Autocatalytic Decomposition Characteristics and thermal decomposition of benzoyl peroxide by differential scanning calorimetry (DSC), and calculated the kinetic parameters of the decomposition process by Kissinger method; Suranee [22] et al Evaluated the thermal hazard and reactivity of hydrogen peroxide with a mass concentration of 35% by DSC. It is found that the calculated activation energy is 70.03 kJ/mol, and the adiabatic temperature rise at heating rates of 2,4,8℃/min is 236.5,159.2,217.5k.…”
mentioning
confidence: 99%
“…For example, Xia, et al 20 and others studied the thermal decomposition characteristics and thermal risk of three anthraquinone hazardous waste by differential scanning calorimetry (DSC), calculated the kinetic characteristics of the decomposition process by Friedman method, and the effect of the coupling of phase transition and decomposition on the thermal risk of materials was studied. Yabei Xu et al 21 studied the Autocatalytic Decomposition Characteristics and thermal decomposition of benzoyl peroxide by differential scanning calorimetry (DSC), and calculated the kinetic parameters of the decomposition process by Kissinger method; Suranee et al 22 Evaluated the thermal hazard and reactivity of hydrogen peroxide with a mass concentration of 35% by DSC. It is found that the calculated activation energy is 70.03 kJ/mol, and the adiabatic temperature rise at heating rates of 2, 4, 8 °C/min is 236.5, 159.2, 217.5 k.…”
mentioning
confidence: 99%